Dimension of e-services quality influencing online purchase intention at CJ Wow Shop / Ahmad Najmi Ahmad Basir, Farisa Nadjeehah Norhasman and Siti Ummirah Zaidi - Ahmad Basir, Ahmad Najmi; Norhasman, Farisa Nadjeehah; Zaidi, Siti Ummirah (2020)
Nowadays, home shopping has become one of the interactive ways to shop. There are various methods that customers may use to make purchases and one of the methods is through the Internet. This study adapted SERVQUAL dimensions into E-SERVQUAL which consisting of 5 most highlighted dimensions in the previous studies. The 5 dimensions of E-SERVQUAL are efficiency, fulfilment, security, aesthetic and responsiveness. The study will identify the relationship and how the dimensions will affect the online purchase intention of CJ Wow Shop customers. The responses was gathered from 101 customers of CJ Wow Shop, responding to the items based on their previous experiences. The result obtained from the survey was that they were positively agreed on most of the statements from each dimension. The result indicated that there are significant positive relationship between E-SERVQUAL dimensions with online purchase intentions. Among all dimensions, website efficiency and website security has the positive relationship with online purchase intentions and at the same time summarizing good response from the customers showing that they have experienced the efficiency and security through their purchasing journey on CJ Wow Shop website. Thus, only 37% of variance was determined for the independent variables to represent the online purchase intentions.